Socio-cultural and economic factors influencing adolescents' resilience against the threat of teenage pregnancy: a cross-sectional survey in Accra, Ghana. Issue 1 (December 2015) - Ahorlu, Collins; Pfeiffer, Constanze; Obrist, Brigit
Abstract Background Adolescent pregnancy exposes female adolescents to medical, social and economic risks. In Ghana, adolescent mothers are more likely to experience complications during pregnancy and delivery as compared to older mothers. This study examined the competencies of adolescent girls to either proactively prevent teenage pregnancy or reactively cope effectively with it. Methods A cross-sectional survey approach was used to interview 820 adolescent girls aged 15–19 years in Accra, Ghana. The main focus of the study was to examine how social capital (various kinds of valued relations with significant others), economic capital (command over economic resources, mainly cash and assets), cultural capital (personal dispositions and habits; knowledge and tradition stored in material forms and institutionalized) and symbolic capital (honour, recognition and prestige) contribute to the development of competencies of adolescents to deal with the threat of teenage pregnancy and childbirth. Results Out of 820 adolescents interviewed, 128 (16 %) were pregnant or mothers. Adolescents in both groups (62 % never pregnant girls and 68 % pregnant/young mothers) have access to social support, especially from their parents. Parents are taking the place of aunts and grandmothers in providing sexual education to their adolescent girls due to changing social structures where extended families no longer reside together in most cases. More (79 %) pregnant girls and young mothers compared to never pregnant girls (38 %) have access to economic support (P = <0.001). Access to social, economic and cultural capitals was associated with high competence to either prevent or deal with pregnancy among adolescent girls. Conclusion Findings showed that adolescent girls, especially those that get pregnant should not be viewed as weak and vulnerable because many of them have developed competencies to cope with pregnancy and childbirth effectively. Thus, focusing on developing the competencies of girls to access social, economic and cultural capitals may be an effective way of tackling the threat of teenage pregnancy than focusing only on their vulnerability and associated risks.